2017
DOI: 10.1186/s13104-017-2615-8
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline-induced ventricular tachycardia: a case report

Abstract: BackgroundIn Bangladesh, each emergency physician faces amitriptyline overdose nearly a day. An acute cardiovascular complication, one of the worst complications is mainly responsible for the mortality in tricyclic overdose. Recently, we managed ventricular tachycardia in a young female presented with an impaired consciousness 10 h after intentionally ingesting 2500 mg amitriptyline. Here, we report it, discuss how the electrocardiography is vital to acknowledge and predict it and its’ complications and also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Medications causing QTc-prolongation are used in both inpatient and outpatient settings and have been thoroughly studied. 1,[5][6][7] While drug-induced QTc-prolongation is recognized due to the potential for Torsades de Pointes (TdP), 7 literature for many other drug-induced arrhythmias is limited to case reports [8][9][10][11][12] outside of drug-induced arrhythmia reviews with atrial fibrillation 13 and bradyarrhythmias. [14][15][16] A newly published review of drug-induced arrhythmias did add further to the literature by including a section on atrioventricular nodal reentrant tachycardia.…”
Section: Introductionmentioning
confidence: 99%
“…Medications causing QTc-prolongation are used in both inpatient and outpatient settings and have been thoroughly studied. 1,[5][6][7] While drug-induced QTc-prolongation is recognized due to the potential for Torsades de Pointes (TdP), 7 literature for many other drug-induced arrhythmias is limited to case reports [8][9][10][11][12] outside of drug-induced arrhythmia reviews with atrial fibrillation 13 and bradyarrhythmias. [14][15][16] A newly published review of drug-induced arrhythmias did add further to the literature by including a section on atrioventricular nodal reentrant tachycardia.…”
Section: Introductionmentioning
confidence: 99%
“…The neurological symptoms of amitriptyline intoxication include lethargy, coma, convulsion and bilateral loss of light reflexes [4]. In addition to the common cardiovascular abnormalities, such as sinus tachycardia and ventricular arrhythmias, patients with amitriptyline intoxication often show the widening of QRS complexes in electrocardiogram (ECG) [4,25], which eventually leads to fatal cardiac arrest. Using rabbit or canine models, earlier studies revealed the ECG abnormalities caused by different doses of amitriptyline to determine its cardiotoxicity [11,27,32].…”
mentioning
confidence: 99%
“…This is due to its effect on atrioventricular conduction through the blockage of fast sodium channels and the inhibition of potassium channels [ 9 ]. Without intervention, fatal dysrhythmias, such as bradycardia with second or third-degree heart block, asystole, and even sudden cardiac death may occur [ 8 - 10 ].…”
Section: Discussionmentioning
confidence: 99%